Efficacy, Safety and Tolerability Of Valsartan Plus HCTZ in Patients With Essential Hypertension: A Multicentre Observational Study in Bangladesh - Islam, MN (Cardiovascular Journal, 2010)
Background: Valsartan is an established drug for treatment of essential hypertension. It blocks the action of Angiotensin II irrespective of its sources. A large proportion of patients need additional treatment with two or more drugs of different pharmacological classes for achieving target blood pressure. Published evidence demonstrated synergistic effect of Thiazides with ARB. Coadministration of valsartan and Hydrochlorothiazide has the potential to reverse the untoward effect of each other. Current study aimed at evaluating the efficacy, safety and tolerability of Valsartan plus Hydrochlorothiazide combination, and thus validating the regimen in the treatment of essential hypertension in Bangladeshi population, a population significantly different from Caucasian population where most studies were done. Methods: Current study is a prospective interventional study involving 404 Adult, patients, with Stage I (SBP 140-159 mmHg/DBP 90-99 mmHg) or Stage II (SBP≥160 mmHg/DBP ≥100 mmHg) essential hypertension or patients uncontrolled on current mono-therapy or other combination therapy. Valsartan plus HCTZ 80/12.5 mg once daily tablet were prescribed to continue till the following visit or for the remainder of the study. In case of inadequate control increment in dose was made on the following visit. Patients were assessed at baseline, at 4th weeks, 12th week and 24th week. One of the major outcome parameter set for the study was the percentage of participant having BP controlled that is a SBP <140 mmHg and DBP <90 mmHg or a reduction >10 mmHg for DBP and/ or >20 mmHg SBP versus baseline values at 24 weeks. At final follow-up, in addition to repetition of the baseline measurements and examinations, data on Safety of the drug was collected by enquiring and recording all adverse events or serious adverse events. Global assessment of efficacy and tolerability of treatment was also done by both the physicians and patients on a 4-point scale. Result: The percentage of participant having BP controlled at the end of the trial was 91%. Besides, Significant reduction in mean SBP and mean DBP was also evident (P<.001) through paired comparison from baseline to end of the study. Average reduction of 32.4 ± 19.5 mmHg was seen in systolic BP and 17.4 ± 9.3 mmHg in diastolic BP. Global assessment based on both physician and patients reported greater satisfaction with the efficacy of treatment modality. Total adverse event reported by only six (1.5%) participants. Of the six cases three of the adverse effect was reported at 3rd visit and another three were reported at 4th visit. Total five dropouts (1.24%) were reported of which 1 in 3rd visit and 4 in 4th visit. Among the dropout patient three were withdrawn from the study and two didn’t attend the final follow-up. Global assessment of safety and tolerability based on both physician and patient’s opinion reveals greater satisfaction level with the safety and tolerability of combination treatment. Conclusion: The combination of valsartan and hydrochlorothiazide is an effective treatment for patients with essential hypertension. The combination is also effective in patients not responding to monotherapy with either agent. The drug is found to be well tolerated with minimal adverse event during the course of treatment. Key words: Valsartan; Hydrochlorothiazide; Hypertension. DOI: 10.3329/cardio.v3i1.6425 Cardiovasc. j. 2010; 3(1): 37-44